Real Collaboration : What It Takes for Global Health to Succeed - Rosenberg, Mark L., 1945- (Book collections on Project MUSE., 2010)
"Essential reading for those who work in global health, this practical handbook focuses on what might be the most important lesson of the last fifty years: that collaboration is the best way to make health resources count for disadvantaged people around the world. Designed as a learning resource to catalyze fresh thinking, Real Collaboration draws from case studies of teams struggling to combat smallpox, river blindness, polio, and other health threats. In honest appraisals, participants share their missteps as well as their successes. Based on these stories, as well as on analyses of many other enterprises, this accessible, engaging book distills the critical factors that can increase the likelihood of success for those who are launching or managing a new partnership"--Provided by publisher.